2001
DOI: 10.4319/lo.2001.46.2.0345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land use and riparian flowpath on delivery of dissolved organic carbon to streams

Abstract: A set of near-stream flowpaths in pasture, native forest and exotic pine plantations in New Zealand was sampled to describe differences in dissolved organic carbon (DOC). The quantity and bioavailability of DOC varied among flowpaths in different land uses, with higher concentrations of DOC in near-stream flow paths than the parent groundwater emerging from the hillslope. Tiles incubated in these waters did not consistently yield higher bacterial growth rates than tiles incubated in groundwaters. DOC compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 46 publications
8
78
1
3
Order By: Relevance
“…Wetlands showed a positive correlation with respect to biotic integrity, as reported by other authors (Roth et al, 1996;Fitzpatrick et al, 2001). Vegetation in wetlands is important for freshwater ecosystems because it reduces excessive light and temperature, growth of algae and aquatic plants, loss of stability of the sediment, nutrient retention, changes in the quantity and quality of organic matter, and alteration of the trophic structure of the system (Findlay, Quinn, Hickey, Burrell, & Downes, 2001).…”
Section: Discussionsupporting
confidence: 58%
“…Wetlands showed a positive correlation with respect to biotic integrity, as reported by other authors (Roth et al, 1996;Fitzpatrick et al, 2001). Vegetation in wetlands is important for freshwater ecosystems because it reduces excessive light and temperature, growth of algae and aquatic plants, loss of stability of the sediment, nutrient retention, changes in the quantity and quality of organic matter, and alteration of the trophic structure of the system (Findlay, Quinn, Hickey, Burrell, & Downes, 2001).…”
Section: Discussionsupporting
confidence: 58%
“…greater relative areas of peat soil and forestry (the Srahrevagh) were significantly higher than the other two monitoring sites, a difference that was consistent both seasonally and over the six years of the study. Colour, and therefore DOC, in these headwater rivers originates almost exclusively from the surrounding catchment soils and the quantity of DOC exported during the study was shown to be a function of catchment properties such as the extent of peat within catchments (Hope et al, 1997a), land use (Findlay et al, 2001), local runoff (Dillon and Molot., 2005) vegetation type (Sobek et al, 2007) and the 5 morphology and geology of the catchment landscape (Moore, 1998). Forestry is also known to influence DOC release from soils and it has been observed that both afforestation and forest clear-felling result in increased DOC concentrations and that these increases may continue for several years after the initial event (DeFries & Eshleman., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(Table 2, Vihinen and Mäntsälä, 1989;Sinsabaugh et al, 1991;Arpigny and Jaeger, 1999;Makoi and Ndakidemi, 2008;Sinsabaugh et al, 2008). Fluorometric enzyme assays were performed under standardized conditions as described before (Findlay et al, 2001). All values were corrected for quenching and potential autofluorescence, that is, because of the presence of small mineral particles, and subsequently standardized to OM.…”
Section: Enzyme Assaysmentioning
confidence: 99%